Efficiency and effectiveness in the control of public management. Effects in the control of environmental public management - Alianak, Raquel Cynthia (Universidad Nacional del Litoral, 2014)
The paper analyzes how the internal control scheme of public management and specifically of environmental public management, is not a task to be performed once a year when the auditors arrive, but should represent a real commitment within each government body, at all hierarchical levels, so that each of them meets the role that has the authority to, in the control of plans, programs and projects to verify their developments and the achievement of the proposed results. We emphasize and insist on the fabulous tool of free access to information (and here we have the social control of public management), involving not only the data that citizens may ask to be informed, but also all the information that must be furnished within what has been called " active transparency " in the budget, financial aspects, and the concrete results of programs, plans and certain public policies. In short, we promote greater democratization of public administration; effective accountability; greater social participation in their control, and greater mutual responsibilities.